Re-imaging and re-conceptualize Hyper Terrorism in Indonesia: based on the Baudrillard framework - Sabar, Alexander; Mustofa, Muhammad; Meliala, Adrianus Eliasta (Technium Social Sciences Journal, 2023)
Hyper-Terrorism in Indonesia has a strong relationship with the phenomenon of cyber terrorism. One of the primary uses of the internet by terrorist groups is to spread propaganda. Propaganda is a utility of hyperspace that is very useful for terror groups, especially in Indonesia. Propaganda carried out by terrorists is generally multimedia communication in the form of instructions, practical and ideological explanations, and justification or promotion of terrorist activities. These can take the form of virtual messages, presentations, electronic magazines, fatwas of ulama-supporting terrorists, audio-video files, and video games, all developed by terrorist organizations and their sympathizers. The terrorist group uses the internet for funding, training, and propaganda (including recruitment, radicalization, and incitement). In Jeans Baudrillard’s concept, communication technology has given birth to a world of media that exists in parallel with reality, breaking the traditional linguistic relationship of sign and meaning, which he calls simulacra with hyperreality as the main characteristic. The big problem now is that there is no in-depth study on the definition of Hyper-Terrorism or the parameters in categorizing information as hyper-terrorism as a feature of the ’Simulacrum of Terror.’ Examining the stages in the simulacrum of terror by Baudrillard, there is a missing stage between the results of media reproduction and the phenomenon of the simulacrum of terror. This research will take up the gap that Baudrillard missed. Then it becomes crucial to study academically, especially regarding the phenomenon of Hyper-Terrorism itself, namely hyperreality in terrorism propaganda, where the reproduction of information that is published globally brings up a relative representation.